Pemanfaatan Aplikasi E-Social Learning dalam Upaya Internalisasi Nilai Kearifan Lokal Gusjigang pada Pembelajaran IPS di MTs NU Hasyim Asy`ari 2 Kudus - Farohi, Ahmad; Wiyanarti, Erlina (IJTIMAIYA: Journal of Social Science and Teaching, 2024)
The aim of this research is to review the use of the Android app E-Social Learning in social studies education, as a step towards internalizing the values of local wisdom Gusjigang. The research methodology employed is qualitative with a field study approach. Primary data collection was conducted through fieldwork using observations and interviews, while secondary data was gathered from relevant previous research literature. Credibility testing was performed using the Triangulation technique. Data analysis followed the steps outlined by Miles and Huberman, including data reduction, data display, and verification. The results of this study indicate that the use of the E-Social Learning application to internalize the values of local wisdom Gusjigang in social studies education is carried out in three stages: planning, implementation, and evaluation. Teachers and students responded positively and enthusiastically to this method of learning, citing the integration of local wisdom Gusjigang with technology as a key factor. SWOT-based evaluation identified strengths in preventing student boredom during the learning process, weaknesses related to reliance on internet connections and device specifications, opportunities for students to learn about culture through integration with technology, and threats including potential reluctance to open and read books, as well as increased dependence on smartphones. This research provides a new contribution to the development of teaching methods that integrate local culture with modern technology. The SWOT-based evaluation used in this study provides profound insights into the strengths, weaknesses, opportunities, and threats associated with the application of technology in local cultural education.